A case of nephrotic syndrome associated with relapsing hepatitis A - Ataş, Bülent; Tuncer, Oǧuz; Çaksen, Hüseyin; Arslan, Şükrü (Journal of Pediatric Infectious Diseases, 2007)
Viral hepatitis A infection is a self-limited infection occurring predominantly among children usually as an anicteric often-subclinical illness. Almost all patients with hepatitis A virus infection recover completely. However, a relapsing course can occur with clinical signs, symptoms and biochemical findings of hepatic inflammation one or four months after the acute phase. In this article, we report a case of nephrotic syndrome associated with relapsing hepatitis A. Although it has been reported that hepatitis A can lead to nephrotic syndrome, an association of relapsing hepatitis A and nephrotic syndrome has not been reported in the literature to the best of our knowledge.
Keywords: Nephrotic syndrome; relapsing hepatitis A